A robustness analysis of the bonding process of joints in wind turbine blades. (October 2018) - Spangenberg, J.; Uzal, A.; Nielsen, M.W.; Hattel, J.H.
Abstract: In this paper, a numerical model is used to perform a robustness analysis of the bonding process of a joint between the two shells composing a wind turbine blade. The flow behaviour of the bonding adhesive is quantified on a rheometer and the Herschel-Bulkley material model is utilized to approximate the rheological data set. The material model parameters are implemented in the numerical model, which is validated by comparison with experimental results. The robustness analysis is focused on analysing the adhesive position and initial shape as well as the inclination angle's effect on the squeeze force and final adhesive geometry. The results illustrate that the numerical model can assist in increasing the strength of the joint, decreasing the risk of residual stress induced cracks, and minimizing cost/waste and mass of the blade.